'Make it another for me and my mates': Does social capital encourage risky drinking among the Danish general population?. Issue 3 (May 2016) - Seid, Abdu k.; Hesse, Morten; Bloomfield, Kim
Aims: The aim of this study was to examine the relationship between several indicators of social capital and risky single occasion drinking (RSOD) in a representative survey sample of the Danish general population. Methods: Data from the 2011 Danish national survey ( n =2569) with respondents aged 15–79 years were used. Ordered logit modelling was applied to investigate the influence of social networks, social support, social participation and trust on RSOD. Results: A strong positive relationship was found between frequency of contact with male friends and RSOD between both sexes. Furthermore, social trust among men and membership in voluntary organisations among women was significantly associated with RSOD. Additionally, contact with male family members for women and active participation in religious services for both sexes were strongly and negatively correlated with RSOD. Conclusions: Some aspects of social capital can be positively related to at-risk health behaviours, as was found for RSOD in the Danish general population.